Historical elements of the behavior therapy from Skinner’s and Ferster’s contribution (Brazilian Journal of Behavioral and Cognitive Therapy, 2019)
The present article revised two sets of papers published during the second half of the twentieth century toshow that fundamental behavior analysis principles were not abandoned and are still being used in clinicalcontext, especially in Brazil. The first set is a review of B.F. Skinner’s main analysis referring clinical therapy;the second set describes both papers written by C.B. Fester about clinical proceeding. The topics deliberatedby those authors are essential for practicing Behavior Analytic Therapy (TAC), with special importance forthe Brazilian TAC. Some topics are relevant due to being a starting point for nowadays developments, whileothers still prevailing as clinical subjects of discussion. Also, a brief history of how TAC was described inother languages is presented, including its effect on Brazilian behavior analysis history. Revisiting this sets ofpapers allowed us to set out components that are still present in clinical practice, specially TAC, such asexplaining client’s behavior in contingencies, teaching him to analyze its own behavior, methods ofintervening during a clinical session, among others. It was possible to conclude that fundamental elements ofBehavior Analysis are still present in clinical practice, particularly in Brazilian TAC.
Keywords: Brazilian behavior analytic therapy; Skinner; Ferster